Informing Inclusive Practice in Post-Secondary Environments: Perspectives of Post-Secondary Instructors with Learning Disabilities - Amy Domenique Gadsden; Lauren Denise Goegan (Canadian Journal for the Scholarship of Teaching and Learning, 2023)
This paper offers post-secondary instructors an opportunity to think about teaching practices and strategies for meaningful inclusion of students with learning disabilities (SLD) in post-secondary environments (PSE). Utilizing the narratives of the authors and building on the principles of Universal Design for Learning (UDL), it provides recommendations for effective inclusive pedagogy for instructors to consider. These recommendations are framed by the three main UDL guidelines of multiple means of engagement, representation, and of action and expression (CAST, 2011). By approaching teaching and assessment in this way, instructors may engage learners authentically, thus reducing the potential for disengagement and subsequent underachievement. This may also facilitate an equitable environment where students can participate in meaningful ways. Finally, instructors may have more time available in class to address student questions and provide support.